Role of age and health in perceptions of returning to work: a qualitative study - Joanne Neary; Srinivasa Vittal Katikireddi; Judith Brown; Ewan B. Macdonald; Hilary Thomson (BMC, 2019)
Abstract Background People aged over 50 years form a growing proportion of the working age population, but are at increased risk of unemployment compared to other age groups. It is often difficult to return to work after unemployment, particularly for those with health issues. In this paper, we explored the perceptions, attitudes, and experiences of returning to work after a period of unemployment (hereafter RTW) barriers among unemployed adults aged over 50 years. Method In-depth semi-structured interviews were conducted with a diverse sample of 26 unemployed individuals aged 50-64 years who were engaged with the UK Government's Work Programme. Data were thematically analysed. Results Age alone was not discussed by participants as a barrier to work; rather their discussions of barriers to work focused on the ways in which age influenced other issues in their lives. For participants reporting chronic health conditions, or disabilities, there was a concern about being unfit to return to their previous employment area, and therefore having to "start again" in a new career, with associated concerns about their health status and managing their treatment burden. Some participants also reported experiencing either direct or indirect ageism (including related to their health status or need to access healthcare) when looking for work. Other issues facing older people included wider socio-political changes, such as the increased pension age, were felt to be unfair in many ways and contradicted existing expectations of social roles (such as acting as a carer for other family members). Conclusion Over-50s experienced multiple and interacting issues, at both the individual and societal level, that created RTW barriers. There is a need for employability interventions that focus on supporting the over-50s who have fallen out of the labour market to take a holistic approach, working across healthcare, employability and the local labour market, providing treatment and skills training for both those out of work and for employers, in order to create an intervention that that helps achieve RTW and its associated health benefit.